2013
DOI: 10.1371/journal.pone.0058152
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Test of PET Scanners in a Multi-Centre Clinical Trial on Breast Cancer Therapy Monitoring Using 18F-FLT

Abstract: A multi-centre trial using PET requires the analysis of images acquired on different systems We designed a multi-centre trial to estimate the value of 18F-FLT-PET to predict response to neoadjuvant chemotherapy in patients with newly diagnosed breast cancer. A calibration check of each PET-CT and of its peripheral devices was performed to evaluate the reliability of the results.Material and Methods11 centres were investigated. Dose calibrators were assessed by repeated measurements of a 68Ge certified source. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The experience with the 68 Ge phantom prompted us to require a re-calibration in case of an observed BAC variability higher than 3-5%. In this study we did not ship a radionuclide calibrator source along with 68 Ge phantom differently from Bouchet et al [49], who, by combining a radionuclide activity calibration check and a 18 F-filled uniform phantom, demonstrated an interscanner variability of the 11 PET/CT scanners lower than 10%. Therefore, within our experimental framework it was not possible to separate the bias coming from an inaccurate radionuclide calibrator with respect to the bias due to the whole calibration process.…”
Section: Discussionmentioning
confidence: 94%
“…The experience with the 68 Ge phantom prompted us to require a re-calibration in case of an observed BAC variability higher than 3-5%. In this study we did not ship a radionuclide calibrator source along with 68 Ge phantom differently from Bouchet et al [49], who, by combining a radionuclide activity calibration check and a 18 F-filled uniform phantom, demonstrated an interscanner variability of the 11 PET/CT scanners lower than 10%. Therefore, within our experimental framework it was not possible to separate the bias coming from an inaccurate radionuclide calibrator with respect to the bias due to the whole calibration process.…”
Section: Discussionmentioning
confidence: 94%
“…For all tumor SUVs, maximal fluctuations were observed between the shortest replay (R 1.5 or R 2 ) and R 10 . Considering a maximum fluctuation of 10 % as an acceptable level of variation for tumor SUV [ 11 ], the number of patients with tumor SUV fluctuations >10 % (compared to R 10 ) was noted. R 1.5 and R 2 were the replays in which the higher number of patients with SUV fluctuations >10 % was observed, whatever the type of SUV.…”
Section: Resultsmentioning
confidence: 99%
“…Using a reference time of 15 min, Lodge et al [ 20 ] reported similar results with a significant lower bias for the SUV peak compared to the SUV max for the 1-, 2-, 3-, and 4-min images. In our study, large SUV max variations up to 58 % (R 1.5 versus R 10 ) were observed for the same tumor in the same patient, which is obviously unacceptable for response-monitoring purposes, particularly when accumulated to other sources of bias [ 11 , 21 ] and if a threshold value is applied to determine treatment response as with PERCIST criteria [ 3 ]. As previously reported [ 2 , 4 , 22 ], we noted that fluctuations of SUV max also affected threshold method SUV since the VOI was determined by selecting pixel values equal to 41 % of the maximum pixel value.…”
Section: Discussionmentioning
confidence: 98%
“…However, the use of multiple PET/CT scanners may have led to some inconsistency in metabolic metric calculations despite our best effort to calibrate these scanners to be consistent. A calibration comparison study on 11 regularly maintained PET/CT scanners observed good reproducibility and accuracy of all dose calibrators and reported no major deviation across different PET calibration systems [29]. Nevertheless, many quantitative descriptors draw from GTVs, for instance, textural features, have been reported to have limited robustness against multiscanners [30].…”
Section: Discussionmentioning
confidence: 99%